Nearly Singular Integrals in 3D Stokes Flow (Communications in Computational Physics, 2013)
A straightforward method is presented for computing three-dimensionalStokes flow, due to forces on a surface, with high accuracy at points near the surface. The flow quantities are written as boundary integrals using the free-space Green'sfunction. To evaluate the integrals near the boundary, the singular kernels are regularized and a simple quadrature is applied in coordinate charts. High order accuracyis obtained by adding special corrections for the regularization and discretization errors, derived here using local asymptotic analysis. Numerical tests demonstrate theuniform convergence rates of the method.